The Use of the Number in the Teaching-Learning Process of Five-Year-Old Children at Peruvian Educational Institution 1094 - Ortiz Ortiz, Liliana Beatriz (2017)
The article reports on the main results of a master’s degree research project about the experiential strategies for the use of the number from the process of teaching learning in the initial education in five year old children. Methodologically, it corresponds to educational qualitative approach applied projective type. In the investigation instruments like the interview were applied to teachers and family parents and the observation to teachers and children. For information processing, documentary analyses and triangulation of information were used. The results evidence that the teachers reflected contradictions in the handling of the number, besides a limited use of their use in the classroom and indifference for the game and the activities carried out by the children in the school; the children evidenced disposition for the mathematical work during the daily game, demonstrating capacity of astonishment, attention and enjoyment. As a contribution to the solution of the identified difficulties, experiential strategies that favor the learning and practice of the number in the classrooms through communication and culture are proposed.